Intelligence Report on Msungli Area, Bamenda Division, Cameroons Province (Colonial Letters and the Contact of Knowledges, 1921)
This file contains colonial intelligence reports including pictures, maps, and statisics on Msungli Area, Bamenda
Keywords: Archives; Colonisation; Letters; Social norms; Discourse analysis; British Colonisation; Colonial Records; Southern Cameroons; Postcolonial Heritage; Great Britain; Postcolonial Studies